A Brighton Collaboration standardized template with key considerations for a benefit/risk assessment for a soluble glycoprotein vaccine to prevent disease caused by Nipah or Hendra viruses. Issue 38 (7th September 2021) - Eldridge, John H.; Egan, Michael A.; Matassov, Demetrius; Hamm, Stefan; Hermida, Luz; Chen, Tracy; Tremblay, Marc; Sciotto-Brown, Susan; Xu, Rong; Dimitrov, Antony; Smith, Emily R.; Gurwith, Marc; et al.
Abstract: Auro Vaccines LLC has developed a protein vaccine to prevent disease from Nipah and Hendra virus infection that employs a recombinant soluble Hendra glycoprotein (HeV-sG) adjuvanted with aluminum phosphate. This vaccine is currently under clinical evaluation in a Phase 1 study. The Benefit-Risk Assessment of VAccines by TechnolOgy Working Group (BRAVATO; ex-V3SWG) has prepared a standardized template to describe the key considerations for the benefit-risk assessment of protein vaccines. This will help key stakeholders to assess potential safety issues and understand the benefit-risk of such a vaccine platform. The structured and standardized assessment provided by the template may also help contribute to improved public acceptance and communication of licensed protein vaccines.